Exchange Rate Policy and Macroeconomic Stability in Vietnam - Huyen, Tran Thi Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 2, 2018)
Since Jan 4 th 2016, the State Bank of Vietnam (SBV) has applied the central exchange rate regime pegging VND to a basket of 8 currencies, which reflects the adaptation of macro policies in general, exchange rate policy in particular when integration context has changed. In order to propose suitable solutions to administrate exchange rate policy effectively, this article employs the VAR model, in which the relationship between exchange rate and three objectives of exchange rate policy (including prices, output and trade balance) are tested. The data used in this model is quarterly, in the period 2001q1-2017q3. Based on the results of the VAR model, a number of policy implications has been proposed, including: (i) continuing to apply currency basket pegged exchange rate regime; (ii) in stead of choosing to devaluate VND, the SBV should use other exchange rate management tools; (iii) speeding up the development of derivative exchange rate market is necessary to reduce the level of ERPT to the import price index so that helps to control inflation in Vietnam and (iv) the SBV should prioritize the exchange rate policy administration towards price stability through adopting the inflation-targeting monetary policy.